1998
DOI: 10.1016/s0008-6363(98)00074-1
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress in the human common carotid artery as function of age and gender

Abstract: These observations suggest that the reduction in mean wall shear stress with age results from the concomitant increase in diameter in an attempt of the arterial system to limit the reduction in storage capacity of the arterial system with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
104
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 29 publications
16
104
4
Order By: Relevance
“…However, no significant difference between wall shear stress calculated in men and women was observed. This result has been previously demonstrated in the carotid artery (30).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, no significant difference between wall shear stress calculated in men and women was observed. This result has been previously demonstrated in the carotid artery (30).…”
Section: Discussionsupporting
confidence: 87%
“…Finally, it could be pointed out that the absence of characterization of the peak wall shear stress could be a limitation because it has been shown that, at the level of elastic conduit arteries, the peak shear stress can be higher in men than in women at similar mean wall shear stresses (30). However, in our study, if the peak shear stress would have been the main determinant of the flow-mediated response, a higher peak shear stress in men in presence of a similar flowdependent response at the same mean shear stress level would have been associated with a lower flowdependent dilatation in this group when compared at peak shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is kept constant, at least in the short term, thus contributing to the regulation of arterial tone and blood flow in order to meet the metabolic needs of the tissues (Rubanyi et al 1990;Hudlicka and Brown 2009).of the arterial wall and a strong predictor of cardiovascular events and all-cause mortality (Vlachopoulos et al 2010). We have previously reported that in healthy individuals, wall shear stress decreases with age (Gnasso et al 1996), and this finding has been confirmed by others (Schmidt-Trucksäss et al 1999;Reneman et al 1986;Samijo et al 1998).…”
mentioning
confidence: 64%
“…The finding that peak wall shear stress in women remains constant is apparently in contrast with previous cross-sectional studies demonstrating an inverse correlation between wall shear stress and age. In the study by Samijo et al (1998), for example, a significant inverse correlation has been reported both in men and women. However, in that study, restricting the analysis to the older subjects comparable in age with the present population, it can be observed that in women, peak wall shear stress does not decrease.…”
Section: Discussionmentioning
confidence: 92%
“…The peak systolic WSR values measured in vivo with the proposed method are higher than those typically reported in the literature for the common carotid arteries (11,(13)(14)(15)(16)20,22) but within the range of normal values in healthy individuals (1,3,21,(28)(29)(30)(31). Reported ranges of carotid WSR and WSS values in healthy volunteers vary significantly across the literature, in particular when comparing different techniques (11).…”
Section: Discussionmentioning
confidence: 81%